2003
DOI: 10.1590/s1519-566x2003000400005
|View full text |Cite
|
Sign up to set email alerts
|

Tabela de vida ecológica de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae)

Abstract: -This work was carried out aiming to obtain ecological life tables for Bemisia tabaci (Genn.) B-biotype in soybean. For that, successive artificial infestations were done in soybean plants, Glycine max (L.) Merril, FT 2000. Samples were made taking ten leaves randomly with intervals of three days, during eight generations of the whitefly. The number of living, dead and parasited insects and the age distribution were registered for each leaf. In this study the correlation coefficients for egg mortality (0,1954)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
1
Order By: Relevance
“…The results obtained in this work, regarding highest mortality rate in young nymphs and the lowest in the "pupae", corroborate the findings of Albergaria et al (2003) found similar results for B. tabaci with greater mortality in the 2 nd and 3 rd instars but the causes of death were not identified.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in this work, regarding highest mortality rate in young nymphs and the lowest in the "pupae", corroborate the findings of Albergaria et al (2003) found similar results for B. tabaci with greater mortality in the 2 nd and 3 rd instars but the causes of death were not identified.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Hoddle and Soliman (2001), studying the Tetraleurodes perseae whitefly, found that after hatching, the first instar or crawler is most susceptible to mortality factors. In studies of the B. argentifolii whitefly, Albergaria et al (2003) highlighted the fact that the simultaneous contribution of mortality factors in the egg, 1st instar and last nymph instar stages was small when compared with the mortality rate found in the 2 nd and 3 rd instars, i.e. the mortality rate tends to be higher in the intermediate development stages.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with several other studies focusing on ecological life tables which have found this immature stage (larvae for holometabolic insects) as the most vulnerable to the action of natural factors (Pereira et al ., 2007). This is because this stage has a longer period for development, compared to stages such as egg or pupae, and therefore is more exposed to biotic and abiotic factors of mortality (Miranda et al ., 1998; Albergaria et al ., 2003; Naranjo & Ellsworth 2005). In the particular case of T. limbata , two distinct periods could be identified during the nymph stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple and overlapping generations of B. tabaci pose significant problems, the sessile nature of immature stages provides an avenue for developing robust, cohort-specific life tables (Naranjo and Ellsworth 2005). To date, field-based life tables have been developed for B. tabaci on cotton (Horowitz et al 1984, Naranjo andEllsworth 2005;Naranjo et al 2004;Naranjo, Ellsworth and Cañas unpublished data;Naranjo 2009), cassava (Asiimwe et al 2007), soybean (de Albergaria et al 2003), cucumber (Shen et al 2005b), cantaloupe, broccoli, alfalfa, ornamental lantana, and various annual weeds (Naranjo et al 2004;Naranjo, Ellsworth and Cañas unpublished data). Hoddle and van Driesche (1996) developed life tables for B. tabaci on poinsettias, but these were done in experimental greenhouses to assess the impact of augmentative biological control with parasitoids.…”
Section: Life Tablesmentioning
confidence: 99%